2011
DOI: 10.1111/j.1600-0722.2011.00911.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of calcium phosphate formation by amelogenins under physiological conditions

Abstract: Amelogenin is essential for proper enamel formation. The present in vitro study extends our previous work at low (10 mM) ionic strength (IS) by examining the effect of amelogenin on mineralization under higher (162 mM) IS conditions found in developing enamel. Full-length phosphorylated (P173) and non-phosphorylated (rP172) amelogenins were examined, along with P148 and rP147 that lack the hydrophilic C-terminus. Calcium phosphate formation was assessed by pH change, while minerals formed were characterized us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 34 publications
6
35
1
Order By: Relevance
“…Although the inhibitory effect of truncated P148 on in vitro mineralization was also found to be concentration dependent, P148 did not similarly guide ordered mineral formation when present at lower concentrations, like full-length P173 . This difference in effects on mineralization may again be related to prior findings showing that truncated P148 and its recombinant analogues from pig (rP147) and mouse (rM166) form random protein assemblies (Fang et al 2011;Kwak et al 2011;Wiedemann-Bidlack et al 2011). In contrast, full-length P173, rP172, and rM179 (from mouse) undergo a stepwise hierarchical self-assembly process from monomers to nanospheres (Fang et al 2011;Fang et al 2013) to more highly ordered chain-like structures (Aichmayer et al 2005;Aichmayer et al 2010;Wiedemann-Bidlack et al 2011).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Although the inhibitory effect of truncated P148 on in vitro mineralization was also found to be concentration dependent, P148 did not similarly guide ordered mineral formation when present at lower concentrations, like full-length P173 . This difference in effects on mineralization may again be related to prior findings showing that truncated P148 and its recombinant analogues from pig (rP147) and mouse (rM166) form random protein assemblies (Fang et al 2011;Kwak et al 2011;Wiedemann-Bidlack et al 2011). In contrast, full-length P173, rP172, and rM179 (from mouse) undergo a stepwise hierarchical self-assembly process from monomers to nanospheres (Fang et al 2011;Fang et al 2013) to more highly ordered chain-like structures (Aichmayer et al 2005;Aichmayer et al 2010;Wiedemann-Bidlack et al 2011).…”
Section: Discussionmentioning
confidence: 76%
“…Calcium and pH-adjusted phosphate (pH 10.9) solutions were sequentially added to protein solutions, as previously described (Kwak et al 2009;Kwak et al 2011). The final solutions contained 2.5 mM calcium (CaCl 2 ), 1.5 mM phosphate (KH 2 PO 4 ), and 1 mg/mL amelogenin (final volume = 0.03 mL).…”
Section: Mineralization Studies With and Without Added Mmp20mentioning
confidence: 99%
“…The precise pH value was selected by design so that the reaction solution would have an initial pH ∼7.4 at 37°C upon mixing all solution components. A liquots of calcium and pH-adjusted phosphate solution were sequentially added to protein solutions to yield final concentrations of 2.5 mM Ca 2+ , 1.5 mM P i , and 0.2 - 2.0 mg/mL protein, with a final volume of 60 μL, as previously reported (3, 5). Samples were then placed in a thermostatic water bath adjusted to 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Although phosphorylation has been found to affect the self-assembly full-length amelogenin in subtle but potentially important ways, it has a marked effect on crystal formation ( e.g ., 3, 4). While oriented, well-organized bundles of crystals are observed in the presence of rP172, P173 was found to stabilize initially formed nano-particles of amorphous calcium phosphate (ACP) and prevent HA formation for up to 3 days in vitro (3, 4). Recently, however, we have found that P173 cleavage by MMP20 (enamelysin) can induce the transformation of stabilized ACP into ordered bundles of HA crystals, suggesting that the formation of the hierarchical enamel structure may be regulated by the proteolysis of full-length native amelogenin, during the early stages of enamel formation [unpublished findings].…”
Section: Introductionmentioning
confidence: 99%
“…In light of these amelogenin-MMP-20 interactions, MMP-20 was proposed to: (i) control amelogenin self-assembly, (ii) decrease amelogenin-apatite binding affinity, (iii) control ACP to apatite phase transformation by amelogenin, 110 and/or (iv) prevent unwanted protein occlusion inside apatite crystals. 111 …”
Section: Amelogenin and Its Targetsmentioning
confidence: 99%